2014
DOI: 10.3758/s13423-014-0702-6
|View full text |Cite
|
Sign up to set email alerts
|

Local Navon letter processing affects skilled behavior: A golf-putting experiment

Abstract: Expert or skilled behaviors (for example, face recognition or sporting performance) are typically performed automatically and with little conscious awareness. Previous studies, in various domains of performance, have shown that activities immediately prior to a task demanding a learnt skill can affect performance. In sport, describing the to-be-performed action is detrimental; whereas in face recognition, describing a face or reading local Navon letters is detrimental. Two golf-putting experiments are presente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 32 publications
1
10
2
Order By: Relevance
“…Additionally, the present results seem to contradict the idea that any shift from procedural to conscious processing can result in the creation of a procedural interference effect, although there are a few important reasons why the procedural interference findings from previous research (Flegal & Anderson, 2008;Lewis & Dawkins, 2015) might not be directly translatable to the musical memorization task used here. First, the memory task in this experiment did not address the fundamental motor processes involved in playing a string instrument, while the novel golf-swing task used in the two aforementioned studies seems to more directly address fundamental golfing technique.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Additionally, the present results seem to contradict the idea that any shift from procedural to conscious processing can result in the creation of a procedural interference effect, although there are a few important reasons why the procedural interference findings from previous research (Flegal & Anderson, 2008;Lewis & Dawkins, 2015) might not be directly translatable to the musical memorization task used here. First, the memory task in this experiment did not address the fundamental motor processes involved in playing a string instrument, while the novel golf-swing task used in the two aforementioned studies seems to more directly address fundamental golfing technique.…”
Section: Discussioncontrasting
confidence: 99%
“…Although these situations are notably different from a music student verbalizing about a new piece of music, as the music student is not verbalizing about the procedural movements involved in playing an instrument, there is evidence that any cross modal verbalization activity could impair procedural memory. Lewis and Dawkins (2015) found a similar overshadowing effect in intermediate golfing performance when participants were asked to locally identify Navon letters 2 or when they were asked to identify faces. These findings indicate that the overshadowing effect is not due to the relationship between the procedural task and verbalization material, but instead could be the result of a switch from an implicit form of processing to a more active, explicit form of processing, as originally suggested by F. Schooler, Fiore, and Brandimonte (1997).…”
mentioning
confidence: 67%
See 2 more Smart Citations
“…Repeatedly identifying the large letter induces global processing, whereas repeatedly identifying the small letter induces local processing (see, also, Lim & Goh, 2013). Global versus local processing styles have been successfully induced in various studies via this approach and were found to differentially impact such subsequent tasks as face recognition (Macrae & Lewis, 2002), eyewitness identification (Perfect, Dennis, & Snell, 2007), and golf-putting performance (Lewis & Dawkins, 2015).…”
Section: Global-local Processingmentioning
confidence: 99%